Low-temperature degradation of toluene over Ag-MnOx-ACF composite catalyst. Issue 5 (23rd February 2023) - Shi, Jiahui; Liu, Qiang; Liu, Rui; Zhao, Dan; Xu, Ximeng; Cui, Jiahao; Ding, Hui
ABSTRACT: Volatile organic compounds (VOCs) have caused a serious threat to the atmosphere and human health. Therefore, it is of great significance to exploit effective catalytic materials for the safe and effective catalytic elimination of VOCs. Herein, Ag-MnOx -ACF composite catalysts were constructed via a two-step impregnation strategy and used for catalytic toluene degradation. A remarkable low-temperature catalytic activity ( T100 = 50℃), excellent stability, as well as CO2 selectivity (80%) were achieved over the Ag-MnOx -ACF catalyst. A series of characterizations indicated that the unique manganese defects structure of birnessite phase manganese oxide played an essential role for toluene oxidation, which was conducive to generating surface adsorbed oxygen. The higher ratio of Mn 3+ /Mn 4+, abundant surface adsorbed oxygen and highly dispersed Ag species were determined to significantly facilitate toluene degradation. The mechanism of efficient degradation of toluene at low temperature was proposed. O3 and H2 O molecules were activated via surface hydroxyl and Mn defects on Ag-MnOx -ACF to produce sufficient OH, enhancing the degradation performance of toluene. We provide a new idea for the catalytic oxidation of benzene VOCs at low even room temperatures. GRAPHICAL ABSTRACT: UF0001